Gene expression profiling of 2 Malaysian Malay male hypertensive subjects - Aqilah Musa. (2017)
Introduction: Hypertension is known as high blood pressure occurred when the blood pressure surpassed 140 mmHg for systolic pressure and 90 mmHg for diastolic pressure. Blood pressure is created by the force exhibited by blood towards walls of blood vessels which depends on cardiac output and resistance of blood vessels. Therefore, increasing blood pressure and vascular resistance will induce hypertension. This unbalanced homeostasis may lead to vascular disease, chronic kidney disease, myocardial infarction, and stroke. In addition. genetics heritability and environment responsible in variance of blood pressure value. The genetics of hypertension is complex which involves many types of genes playing a different role in controlling the blood pressure. In this study, 84 genes were screened with different mechanisms such as vasotone, smooth muscle constriction and relaxation, blood pressure regulation, ion transport, lipid metabolism, renin-angiotensin system and nitric oxide metabolism. Objective: The main objective is to screen the genes expression associated with hypertension among Malay male hypertensive subjects. Method: The blood samples were screened and selected for hypertensive and normotensive subjects. Then, RNA extraction followed by quality test was conducted. RT² First Strand Kit was used in reverse transcription process to synthesize the cDNA. Then. RT² SYBR Green ROX FAST Master Mix with cDNA was mixed for fluorescence attachment. The mixture was loaded into each well of PCR Array plate and continued with real-time polymerase chain reaction. Lastly, data and statically analysis were done by PCR Array Systems. Result: The results showed 44 genes were over-expressed and 26 genes were under expressed when compared between hypertensive subjects with normotensive subject. Conclusion: There are many genes control the regulation of blood pressure these genes either act independently or interact with one another. imbalance expressions of these genes were associated with severity development of hypertension in the patients.